Evaluating teacher performance during the pandemic: opinion from Mexican university students - Henriquez Ritchie, Patricio (2023)
Introduction: The evaluation of the performance of university teachers from the opinion of their students is a recurring process, although during the pandemic there are few experiences. Objective: to evaluate the performance of university teachers from the opinion of their students, in the context of a pandemic. Method: representative sample of 673 students from a Mexican public university, a teacher performance questionnaire adapted for virtual classes was used. Results: most of the teachers adapted to an asynchronous virtual work dynamic, although a significant percentage (41.9%) continued to teach classes synchronously (videoconferences). Teachers in initial formative stages mainly promoted individual content learning, contrasting with those in advanced stages, who promoted situated learning. Students with unfavorable opinions regarding content mastery and assessment strategies mentioned the promotion of rote learning, to the detriment of more constructivist learning. The contrasts were statistically significant.